PENGARUH TINGKAT KECERDASAN INTELEKTUAL, EMOSIONAL DAN SPIRITUAL TERHADAP MOTIVASI KERJA DAN KINERJA KARYAWAN PT. SUMBER BUANA MOTOR DI YOGYAKARTA - Tri Ratna Purnamarini (Indonesian Journal of Economics, Entrepreneurship, and Innovation, 2020)
This study aims to determine the effect of the level of intellectual, emotional and spiritual intelligence on work motivation and employee performance of PT. Sumber Buana Motor. This research was conducted with a quantitative approach, to analyze the data on the population of 52 employees and a sample totaling 46 employees with simple random sampling technique. The results showed that, the value of R ² (Y1) 0.173412 mean intelligence variables (X1), emotional (X2) and spiritual (X3) 17.3412% effect on motivation (Y1), the rest influenced other variables. Rated R ² (Y2) 0.180417 mean mean intelligence variables (X1), emotional (X2) and spiritual (X3) 18.0417% impact on employee performance (Y2), the rest influenced other variables. Intellectual level but not significant positive effect on motivation (Y1) and employee performance (Y2). The level of emotional intelligence (X2) significant positive effect on motivation (Y1) with a value of T-statistics of 2.724771, while the impact on employee performance (Y2) positive but not significant. The level of spiritual intelligence (X3) have significant positive impact on employee performance (Y2) with a value of T-statistics of 2.785819, while the motivation (Y1) positive but not significant. So, from these results it can be concluded that there is a significant effect of emotional intelligence on work motivation. And there is significant influence of spiritual intelligence on employee performance.